Pemetaan Muatan Kesehatan Mental Dalam Buku Ajar Pendidikan Agama Islam Jenjang Menengah - Sulisno, Roni; Rahmat, Munawar; Hyangsewu, Pandu (Jurnal Ragam Pengabdian, 2026)
Adolescent mental health requires strategic interventions through Islamic Religious Education (PAI) in schools. However, the mental health content in PAI textbooks has not yet been systematically mapped. This study aims to extract mental health content from six units of analysis, namely the official PAI textbooks for junior high and senior high school levels (Grades VII–XII) under the Merdeka Curriculum. The method used was concept-based qualitative content analysis (QCA) with a hierarchical framework integrating six dimensions of Psychological Well-Being and eight categories of Tazkiyatun Nafs (a total of 14 categories). The results indicate that mental health content is integrated through the six dimensions of Psychological Well-Being and the eight categories of Tazkiyatun Nafs. The distribution of material is gradual: at the junior high school level, the emphasis is on intrapersonal aspects, while at the senior high school level, the focus is on autonomy and the prevention of risky behaviors. However, a representation discrepancy was found: the aspects of spiritual resilience and behavioral control have reached Level 3 (Practice & Evaluation), while self-acceptance and purpose in life remain at Level 2 (Conceptual). The implications of this study underscore the need to transform PAI curriculum materials from normative narratives into practical tools that align spiritual values with mental health literacy, as well as to optimize the “Mari Bermuhasabah” rubric as a medium for psychosocial reflection to bridge the pedagogical gap in the dimension of acceptance.